In Vivo Efficacy of HD0471953: A Novel GPR119 Agonist for the Treatment of Type 2 Diabetes Mellitus - So Ra Kim; Dae-Hoon Kim; Soo Hyun Park; Young Seok Kim; Chun Hwa Kim; Tae-Young Ha; Jin Yang; Jae-Keol Rhee (Journal of Diabetes Research)
G-protein coupled receptor 119 (GPR119) has emerged as a promising new target for the treatment of type 2 diabetes mellitus. The expression of GPR119 on the pancreatic B cells and intestinal L cells provides a unique opportunity for a single drug to promote insulin and GLP-1 secretion. In this study, we identified a novel small molecule GPR119 agonist, HD0471953, from our large library of synthetic compounds based on its ability to anti-hyperglycemic effects on T2DM murine models. We have tested the acute efficacy of HD0471953 by the oral glucose tolerance test (OGTT) with normal C57BL/6J mice. Then, chronic administrations of HD0471953 were performed to evaluate the efficacy on various diabetic rodent models. Single administration of HD0471953 showed improved glycemic control with a dose-dependent manner in OGTT with normal mice, and the insulin and GLP-1 were also increased. To identify chronic efficacy, we have observed a decline of blood glucose and fasting insulin in a dose-dependent manner of 10, 20, and 50 mpk in db/db mice. The results suggest that HD0471953 may be a potentially promising anti-hyperglycemic agent for the treatment of patients with type 2 diabetes mellitus.